Memahami Metode Problem Solving Dalam Al-Qur'an Surah Al-Kahfi Ayat 28 - Ma'ruf, Amar (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2022)
The Qur'an also discusses various aspects, one of which is discussing the stories of the previous people. Which, these stories in the Qur'an have a special position and verses, and even the verses that discuss the story are more than the verses that discuss legal aspects in Islam. From the explanation above, it can be concluded that not only verses about law are capable of solving problems in every problem, but the stories about the previous people in the Qur'an also have their own methods in solving various kinds of problems that occur in the middle of the world. - midst of Muslims. Learning methods are needed to achieve the expected targets during the learning process. For this reason, teachers must be able to choose which method is suitable to be applied to their students in order to get good results and as expected. The Problem Solving method is expected to make students learn to solve problems in the right and appropriate way. This will greatly affect the independence of students when facing problems in their environment.